The Effect Of Individual Characteristics And Organizational Citizenship Behavior (Ocb) On Job Satisfaction With Work Environment As A Moderating Variable - Randini Raya Rabbani; Zulfah Yuliani (Journal of Management and Digital Business, 2024)
Purpose - This study aims to examine how individual and organizational citizenship behavior characteristics affect employee job satisfaction. And assess how the work environment moderates the influence of individual characteristics and organizational citizenship behavior on job satisfaction. Design/methodology/approach - This study uses a quantitative research method, using primary data collected from 2 banking companies. Data analysis was carried out using Partial Least Square (PLS) software with Moderated Regression Analysis. Findings – The findings of this study reveal that the characteristics of individual and organizational citizenship behavior do not increase job satisfaction. The Work Environment functions as a pure moderator that strengthens the relationship between individual characteristics and job satisfaction. Meanwhile, the work environment functions as a homologous moderator with an impact that does not strengthen the relationship between Organizational Citizenship Behavior and job satisfaction. Research limitations/implications - In this study, both variables, namely individual characteristics and organizational citizenship behavior, focus on the behavior of employees, so it is likely that there are many other factors that also influence job satisfaction, and positive behavior is not applied in an organization.